Twenty years of fluorescence imaging of intracellular chloride - Arosio, Daniele; Ratto, Gian Michele (Frontiers in Cellular Neuroscience, 2014)
Chloride homeostasis has a pivotal role in controlling neuronal excitability in the adult brain and during development. The intracellular concentration of chloride is regulated by the dynamic equilibrium between passive fluxes through membrane conductances and the active transport mediated by importers and exporters. In cortical neurons, chloride fluxes are coupled to network activity by the opening of the ionotropic GABAA receptors that provides a direct link between the activity of interneurons and chloride fluxes. These molecular mechanisms are not evenly distributed and regulated over the neuron surface and this fact can lead to a compartmentalized control of the intracellular concentration of chloride. The inhibitory drive provided by the activity of the GABAA receptors depends on the direction and strength of the associated currents, which are ultimately dictated by the gradient of chloride, the main charge carrier flowing through the GABAA channel. Thus, the intracellular distribution of chloride determines the local strength of ionotropic inhibition and influences the interaction between converging excitation and inhibition. The importance of chloride regulation is also underlined by its involvement in several brain pathologies, including epilepsy and disorders of the autistic spectra. The full comprehension of the physiological meaning of GABAergic activity on neurons requires the measure of the spatiotemporal dynamics of chloride fluxes across the membrane. Nowadays, there are several available tools for the task, and both synthetic and genetically encoded indicators have been successfully used for chloride imaging. Here, we will review the available sensors analyzing their properties and outlining desirable future developments.